2022
DOI: 10.1111/1759-7714.14545
|View full text |Cite
|
Sign up to set email alerts
|

Disease monitoring of epidermal growth factor receptor (EGFR)‐mutated non‐small‐cell lung cancer patients treated with tyrosine kinase inhibitors via EGFR status in circulating tumor DNA

Abstract: Objective Circulating tumor DNA (ctDNA) monitoring proves to be a promising approach to assess response and predict survival in epidermal growth factor receptor (EGFR)‐mutated non‐small‐cell lung cancer (NSCLC) patients treated with tyrosine kinase inhibitors (TKIs). However, whether the dynamic changes in ctDNA EGFR mutation status have the same predictive value as ctDNA remains unknown. This study aims to explore the predictive value of dynamic changes in both ctDNA and ctDNA EGFR status. Methods A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…Table 1 presents data on the association between plasma ctDNA/cfDNA EGFR mutations and the efficacy and prognosis of targeted therapy in NSCLC patients [ 28 , 30 , 31 , 32 , 33 , 34 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The BENEFIT trial prospectively demonstrated the feasibility of using liquid biopsy to guide the efficacy of first-line EGFR-TKI therapy for the first time.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%
“…Table 1 presents data on the association between plasma ctDNA/cfDNA EGFR mutations and the efficacy and prognosis of targeted therapy in NSCLC patients [ 28 , 30 , 31 , 32 , 33 , 34 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The BENEFIT trial prospectively demonstrated the feasibility of using liquid biopsy to guide the efficacy of first-line EGFR-TKI therapy for the first time.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%
“…Другим направлением ЖБ, нашедшим широкое применение в практической онкологии, является анализ цоДНК для мониторинга ответа опухоли на терапию и оценки риска рецидивов. Накоплено значительное количество данных о том, что падение уровня цоДНК в крови больных раком легкого на фоне применения противоопухолевых препаратов может расцениваться как благоприятный прогностический признак [45][46][47]. Аналогично длительный мониторинг концентрации и анализ мутаций цоДНК в плазме пациентов с раком прямой кишки на фоне лекарственной терапии позволяет выполнять эффективный контроль течения заболевания [48][49][50].…”
Section: циркулирующая опухолевая днк (цоднк)unclassified
“…Однако на данный момент эта задача, хотя и необычайно многообещающая, все еще носит экспериментальный характер. Можно отметить, что в контексте более рутинной диагностики предварительный отбор ЦОК помогает улучшить детекцию предиктивных мутаций [45,110,117,118]. Кроме того, важно, что выделение ЦОК помогает упростить ЖБ в отношении выявления химерных транскриптов, методики детекции которых в реальной практике обычно основаны на анализе мРНК [119][120].…”
Section: ен имянитов еш кулигина га янусunclassified
See 1 more Smart Citation
“…The field of lung cancer treatment has undergone significant advancements, thanks to the identification of novel targets and continuous refinement of therapeutic approaches. Particularly noteworthy is the emergence of targeted therapies, such as tyrosine kinase inhibitors (TKIs), which have gained recognition for their ability to elicit improved responses with fewer side effects [ 1 3 ]. The development of third-generation TKIs has propelled them to the forefront of first-line therapy for patients with sensitive EGFR mutations, surpassing the efficacy of earlier generations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%